Assessing the nomenclatural history of the sucupira‐branca trees: Friedrich Sellow's (1789–1831) collections, typification and checklist of the Neotropical legume genus Pterodon. Issue 1 (29th October 2022) - Carvalho, Catarina S.; Lima, Haroldo C.; de Moraes, Pedro L.R.; Cardoso, Domingos B.O.S.
Abstract: Sucupira‐branca is a popular name for the papilionoid legume tree genus Pterodon (Leguminosae, Papilionoideae), which is amply distributed across South American savannas and seasonally dry tropical forests. Pterodon has been strongly supported as monophyletic in all molecular phylogenetic analyses and stands out within the Dipterygeae clade by the pinnately compound leaves with terete rachis, symmetrical leaflets with emarginate apex, and indehiscent, one‐seeded cryptosamara fruit. Despite a growing interest in Pterodon species, mainly due to their potential as drug and timber sources, their nomenclature was never fully assessed. Here, we present a nomenclatural review of the economically and ecologically important Pterodon, where we assess all 15 names and designations ever associated with the genus and provide all known orthographic variants and type localities for the accepted names. Besides that, we propose one new species the designation of which has never been validly published, typify five names, propose one new synonym, and provide a list of all the accepted names in the genus. Also, we show that the nomenclatural history of P. emarginatus, one of the ecologically most dominant species in fire‐prone savanna vegetation, is closely related to how Friedrich Sellow (1789–1831) collected and numbered his gatherings. By elucidating the typification of this particularly important species, we shed light on how to more accurately annotate Sellow's specimens in nomenclatural revisions.